Wachstumsdichtemesser in der Sahara: Die Straßenrandvegetation - Gabriel, Baldur; Schmid, Marcelina (ERDKUNDE, 1981)
A noticeable linear concentration of vegetation along pistes and especially asphalt roads (roadside vegetation) has been observed in desert steppes and semi-desert regions of the Sahara. The flora differs in plant density as well as in height, in the variety of species as well as in its freshness from that found away from the driving tracks. The cause of this pattern of growth is seen in an increased supply of water, which is chiefly (but not exclusively) conditioned by the run-off of precipitation water from the road surface.